G20- und EU-Regulierung von Krypto-Assets - Oliver Read (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifi), 2019)
Zur Regulierung von Krypto-Assets sind weitere Schritte unternommen worden. Vor dem G20-Gipfel in Osaka im Juni 2019 hat die Financial Action Task Force einen Leitfaden zur Bekämpfung von Geldwäsche und Terrorismusfinanzierung spezifisch für die Asset- Klasse herausgegeben, während die anderen internationalen Standardsetzer weiterarbeiten. Auf EUEbene wurde die 5. Geldwäscherichtlinie mit Begriffsbestimmungen zu virtuellen Währungen im Juni 2018 verabschiedet. Die European Banking Authority und die European Securities and Markets Authority haben im Januar 2019 Empfehlungen für eine EU-Regulierung von Krypto-Assets an die Europäische Kommission gerichtet. Nun ist die Kommission dran. – – Further steps to regulate crypto-assets have been undertaken. Ahead of the G20 summit in Osaka in June 2019, the Financial Action Task Force published a guidance on Anti-Money Laundering and Countering the Financing of Terrorism specific for this asset class while the other international standard-setting bodies are continuing their work. At the EU level, the 5th Anti-Money Laundering Directive with definitions on virtual currencies was released in June 2018. In January 2019, the European Banking Authority and the European Securities and Markets Authority issued recommendations to the European Commission concerning a EU-regulation of crypto-assets. Now it is the Commission's turn.
Keywords: F53; G18; G28; K42; 330; crypto-assets; virtual assets; virtual currencies; G20; Financial Stability Board; Financial Action Task Force; AML/CFT